Inhibition of 3,4-methylenedioxymethamphetamine (MDMA) metabolism leads to marked decrease in 3,4-dihydroxymethamphetamine (HHMA) formation but no change in serotonin neurotoxicity: Implications for mechanisms of neurotoxicity - Mueller, Melanie (2011)
3,4-Methylenedioxymethamphetamine (MDMA)’s O-demethylenated metabolite, 3,4-dihydroxymethamphetamine (HHMA), has been hypothesized to serve as a precursor for the formation of toxic catechol thioether metabolites (e.g. 5-N-acetylcystein-S-yl-HHMA) that mediate 3,4-methylenedioxymethamphetamine (MDMA) neurotoxicity. To further test this hypothesis, HHMA formation was blocked with dextromethorphan (DXM), which competitively inhibits cytochrome P450 enzyme-mediated O-demethylenation of MDMA to HHMA. In particular, rats were randomly assigned to one of four treatment groups (N= 9–12 per group): 1) Saline/MDMA; 2) DXM/MDMA; 3) DXM/Saline; 4) Saline/Saline. During drug exposure, time-concentration profiles of MDMA and its metabolites were determined, along with body temperature. One week later, brain serotonin (5-HT) neuronal markers were measured in the same animals. DXM did not significantly alter core temperature in MDMA-treated animals. A large (greater that 70%) decrease in HHMA formation had no effect on the magnitude of MDMA neurotoxicity. These results cast doubt on the role of HHMA-derived catechol thioether metabolites in the mechanism of MDMA neurotoxicity.